New records and updated list of the herpetofauna from Luot mountain, Vietnam National University of Forestry, Vietnam - Vuong Quang Vinh; Vu Thi Ngoc Mai; Nguyen Thi Mai; Hoang Thi My Duyen; Dinh Sy Tuong; Nguyen Huyen Thuong; Nguyen Hoang Thi Thuy Nhan; Luu Quang Vinh (Journal of Forestry Science and Technology, 2025)
Luot Mountain, managed by the Vietnam National University of Forestry, spans over 110 hectares and is an important experimental forest. The area features a mixed forest ecosystem, combining monoculture plantations and native species, creating favorable conditions for biodiversity development. It is not only home to a variety of plant and animal species but also serves as a valuable environment for education and research, supporting training programs and nature conservation efforts. In this study, reptiles and amphibians at Luot Mountain were surveyed using the transect method, which helped clarify the richness of the ecosystem. Three reptile species were recorded for the first time, including: Emma’s dragon (Calotes emma), Brahminy Blind Snake (Indotyphlops braminus), and Yellow-Spotted Keelback (Fowlea flavipunctata). These discoveries increased the total number of species recorded at the site to 29, including 19 reptiles and 10 amphibians. Through this research, a total of 5 threatened species were recorded, including 2 species listed in the IUCN Red List (2024), 5 species in the Vietnam Red Data Book (2007), and 2 species in Government Decree No. 84 (2021). These findings highlight the importance of protecting forest ecosystems to ensure sustainability for future generations, emphasizing the need for continuous conservation efforts and scientific cooperation to preserve these valuable habitats for years to come.